2021
DOI: 10.1016/j.xphs.2021.08.024
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive LC-MS/MS Method for Targeted Quantitation of Lipase Host Cell Proteins in Biotherapeutics

Abstract: Identification and accurate quantitation of host cell proteins (HCPs) in biotherapeutic drugs has become increasingly important due to the negative impact of certain HCPs on the safety, stability, and other product quality of biotherapeutics. Recently, several lipase HCPs have been identified to potentially cause the enzymatic degradation of polysorbate, a widely used excipient in the formulation of biotherapeutics, which can severely impact the stability and product quality of drug products. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Detection of low-abundance HCPs in drug products is a major challenge owing to the extremely large dynamic range barrier between HCPs and drug products. This challenge has been overcome with the recent development of HCP analysis technologies in the past few years. ,,, , The lowest detection limit has been improved to 0.002 ppm with the PDLM method developed by Zhang et al Nevertheless, absolute quantification of HCPs that may potentially have negative effects on drug product quality when present at subppm or low-ppm levels still remains a challenge in the pharmaceutical industry. An LC-MRM-based method developed to overcome this challenge has enabled the detection of three high-risk lipases at low-ppm levels in mAb samples. , However, accurate quantification of HCPs at subppm levels remains difficult to achieve but is desirable for evaluating the potential effects of certain HCPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detection of low-abundance HCPs in drug products is a major challenge owing to the extremely large dynamic range barrier between HCPs and drug products. This challenge has been overcome with the recent development of HCP analysis technologies in the past few years. ,,, , The lowest detection limit has been improved to 0.002 ppm with the PDLM method developed by Zhang et al Nevertheless, absolute quantification of HCPs that may potentially have negative effects on drug product quality when present at subppm or low-ppm levels still remains a challenge in the pharmaceutical industry. An LC-MRM-based method developed to overcome this challenge has enabled the detection of three high-risk lipases at low-ppm levels in mAb samples. , However, accurate quantification of HCPs at subppm levels remains difficult to achieve but is desirable for evaluating the potential effects of certain HCPs.…”
Section: Resultsmentioning
confidence: 99%
“…An LC-MRM-based method developed to overcome this challenge has enabled the detection of three high-risk lipases at low-ppm levels in mAb samples. 19,23 However, accurate quantification of HCPs at subppm levels remains difficult to achieve but is desirable for evaluating the potential effects of certain HCPs. We have shown that subppm levels of lipases or esterase cause PS degradation in drug products during long-term storage.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…utilized a targeted LC–MS/MS with high-resolution multiple-reaction-monitoring quantitation method for three lipases PLBL2, LPL, and LIPA for the characterization of process intermediates [ 52 ]. This method demonstrated good sensitivity with lower limit of quantitation (LLOQ) around 1 ng/mL (translated to 0.8 to 2.2 ppm for the three lipases in a product matrix), and linear dynamic range of 3 orders of magnitude for the three lipase HCPs [ 52 ]. The LLOQ of those current targeted HCP quantification approaches is still relatively high compared with the low concentration for these active PSDE species to remain active.…”
Section: Analytical Toolboxmentioning
confidence: 99%